The Possible Role of Helicobacter pylori Infection in Hashimoto’s Thyroiditis - Hamid, Zainab A. (Journal of the Faculty of Medicine Baghdad, 2017)
Background: Autoimmune thyroiditis is one of autoimmune thyroid diseases. The cause of Hashimoto’s thyroiditis is not clearly identified; however, both genetic and environmental are suggested to play a role in pathogenesis of the disease. Helicobacter pylori (H pylori) is one of the possible causative agents.Objectives: The aim of this study is to look for the association of H. pylori infection with Hashimoto’s thyroiditis.Patients and Methods: a case-control study involved patients with Hashimoto’s thyroiditis (n=100) and  control group (hyperthyroidism n=50, healthy persons n=50), the study groups were subjected to serological investigation of anti- H. pyloriIgG antibodies, anti-thyroid peroxidase antibody, and anti-thyroglobulin antibody(anti-TG Ab) using ELISA technique; besides, demographic data were collected from studygroups.Results: Eighty two percent of Hashimoto’s thyroiditis patients were females; 57% of Hashimoto’s  thyroiditis patients were positive for anti- H. pyloriIgG antibodies while the positive result was detected in  only 22% of control group and the results were statistically significant (p